Red blood cell storage lesion. (26th November 2014) - Obrador, Rafael; Musulin, Sarah; Hansen, Bernie
Abstract Objective To summarize current understanding of the mechanisms responsible for changes occurring during red blood cell (RBC) storage, collectively known as the storage lesion, and to review the biological and clinical consequences of increasing storage time of RBCs. Data Sources Human and veterinary clinical studies, experimental animal model studies, and reviews of the RBC storage lesion with no date restrictions. Human Data Synthesis Experimental studies have characterized the evolution of human RBC and supernatant changes that occur during storage and form the basis for concern about the potential for harm from long‐term storage of RBCs. Although 4 randomized controlled trials of varying sizes failed to find an association between RBC storage time and negative clinical outcomes, a recent meta‐analysis and numerous observational clinical studies have demonstrated that transfusion of old versus fresh stored RBCs is associated with an increased risk of morbidity and mortality, particularly among trauma victims and cardiac surgery patients. Potential clinical consequences of RBC transfusion following development of the storage lesion include risk of organ dysfunction, organ failure, infections, and death. Veterinary Data Synthesis Experimental animal models have contributed to the evidence supporting adverse consequences of the RBC storage lesion. Studies on relevant RBC storage issues such as the effect of different preservative solutions and leukoreduction have been completed. Transfusion with RBCs stored for 42 days increases mortality in dogs with experimental sepsis. Conclusion Storage of RBCs induces progressive biochemical, biomechanical, and immunologic changes that affect red cell viability, deformability, oxygen carrying capacity, microcirculatory flow, and recipient response. Most reports in the human and veterinary literature support the concept that there are deleterious effects of the RBC storage lesion, but additional studies with improved experimental design are needed to identify compelling reasons to modify current blood banking and transfusion practices.